Frog medicine - Teague, Mark (New York : Scholastic Inc, 1991)
Elmo Freem can't believe he has to do a book report on a dumb book called Frog Medicine. But suddenly, the book doesn't seem so dumb when he finds himself turning into a frog. Time to go to Frogtown and find the author of the book, where Elmo learns lots about frogs, book reports, and life in general!
Keywords: Frogs-Fiction; Medicines-Fiction